Boron-Doped Diamond Electrodes for Toxins Sensing in Environmental Samples—A Review - Aleksandar Mijajlović; Vesna Stanković; Tijana Mutić; Sladjana Djurdjić; Filip Vlahović; Dalibor Stanković (Sensors)
Boron-doped diamond electrodes have found applications in the detection, monitoring, and mitigation of toxic chemicals resulting from various industries and human activities. The boron-doped diamond electrode is a widely applicable technology in this field, primarily due to its excellent surface characteristics: minimal to no adsorption, a wide operating potential range, robustness, and high selectivity. These extraordinary properties can be further enhanced through surface termination, which can additionally improve the analytical performance of boron-doped diamond (BDD) electrodes. The high accuracy and precision of the developed methods indicate the broad practical applicability of these electrodes across various sample matrices. Some studies have shown that different strategies can lead to enhanced sensitivity and selectivity, such as modifying the electrode surface (nanostructuring), forming different composite materials based on BDD, or implementing miniaturization techniques. Thus, this review summarizes the recent literature on the electroanalytical applications of BDDE surfaces, with a particular focus on environmental applications.